(untitled) (Sains Humanika, 2021)
Productive Welfare and 2 Years Exit Policy (2YEP) approach was established by the Department of Social Welfare Malaysia (JKMM) aim to help clients towards independent living and able to continue their life without relying on financial assistance given by JKMM. The aim of this study is to identify the factors of client engagement and problems faced within implementing entrepreneurship program through “Geran Pelancaran” provided by JKM. Survey methods using questionnaires has been used in this study. A total of 234 respondents were involved in this study through purposive sampling, including 107 respondents from the Northern Zone, and 127 respondents from the Eastern Zone, out of 17 Social Welfare District Offices (PKMD) in both zones. Results showed that the majority of respondents engaged in their own business (85%), especially in food and beverage types business (58.1%). For engagement factors in entrepreneurship, the high mean value is shown by family-bearing items (4.45), deep interest (4.34), and a desire to be independent (4.33). Overall, the mean for respondents’ involvement factors are at a moderate to high level. Respondents also faced some problems before and within doing business especially financial problems, lack of revolving capital, and products that remain unsold. The productive welfare approach and 2 Years Exit Policy (2YEP) program supposed to help increasing revenue and reduce clients’ dependency on JKM’s assistance. However, this study found that 84% of the respondents still has income below the poverty line. Thus, reviewing of the program and continuous monitoring can help clients increase their motivation and thus eradicate poverty among the clients.